2005
DOI: 10.1007/s00383-005-1576-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the site of small bowel resection on intestinal epithelial cell apoptosis

Abstract: Background-Massive small bowel resection (SBR) results in a significant increase in intestinal epithelial cell (EC) proliferation as well as apoptosis. Because the site of SBR (proximal (P) vs. distal (D)) affects the degree of intestinal adaptation, we hypothesized that different rates of EC apoptosis would also be found between P-SBR and D-SBR models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
21
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 25 publications
(36 reference statements)
3
21
0
Order By: Relevance
“…This observation has been confirmed by other investigators (12,(22)(23)(24). Given the highly dynamic nature of the intestinal mucosa, elevated rates of apoptosis probably serve to counter the increased rates of enterocyte proliferation, thus preserving a critical homeostatic balance.…”
supporting
confidence: 74%
“…This observation has been confirmed by other investigators (12,(22)(23)(24). Given the highly dynamic nature of the intestinal mucosa, elevated rates of apoptosis probably serve to counter the increased rates of enterocyte proliferation, thus preserving a critical homeostatic balance.…”
supporting
confidence: 74%
“…Coupled with increased Bax expression (4,13,27,36,38) this finding suggests that the activity of endogenous Bax is also a contributor toward the elevated rates of enterocyte apoptosis observed after SBR. Furthermore, we provide evidence supporting our hypothesis that Bax activation is mediated by p38 MAPK in vivo.…”
Section: Discussionmentioning
confidence: 95%
“…Based on these findings, we have, therefore, focused on elucidating how the intrinsic pathway mediates gut apoptosis during adaptation. Following SBR, increased expression of the proapoptotic protein Bax has been recorded in enterocytes, which correlates with augmented rates of apoptosis (4,13,27,36,38). Furthermore, using Bax-null mice, we have established that Bax expression is required for resection-induced apoptosis (22,37).…”
mentioning
confidence: 96%
“…We found that both ANGII receptors subtypes AT1R and AT2R expressed on intestinal mucosa surface of the rats after small bowel transection or resection. It showed that the minimum immunoreactivity for angiotensin II receptor subtype 1 (AT1R) appeared in the SBS group rats Pediatr Surg Int (2012) 28:533-541 539 intestinal mucosa at 7 days in an SBS mouse model [14]. ACE-I treatment to rats after SBR revealed higher intestinal mucosa structural adaptation.…”
Section: Discussionmentioning
confidence: 98%
“…Intestinal adaptation after SBR in rodents is structurally characterized by an increase in ECs proliferation and apoptosis rates [14,15]. The precise mechanisms for these changes have not been clearly understood.…”
Section: Discussionmentioning
confidence: 99%